Mecanismo de detección de corrupción en compras del Estado: sistema de precios testigo como política pública - Guillén Uyen, Jorge (2014)
The following paper discusses the advantages and disadvantages of implementing a Witness System of Market Prices, system that would solve the problem of overvalued shopping in a reverse auction scheme within countries of Latin America. In this paper we present cases of Witness Prices System that have been applied in countries of the region such as Argentina and Colombia. From the latter experience in Argentina and Colombia, we propose a guideline that can be applied in other countries in the region.